Total body irradiation-based versus busulfan-based myeloablative conditioning for single-unit cord blood transplantation in adults. Issue 5 (16th April 2022) - Konuma, Takaaki; Ooi, Jun; Monna-Oiwa, Maki; Isobe, Masamichi; Tomonari, Akira; Kato, Seiko; Iseki, Tohru; Nannya, Yasuhito; Tojo, Arinobu; Takahashi, Satoshi
Abstract: Comparative studies between total body irradiation (TBI)-based and busulfan-based myeloablative conditioning (MAC) regimens for cord blood transplantation (CBT) have been limited. We retrospectively analyzed the results of single-unit CBT in 333 adult patients who received either TBI-based ( n  = 258) or busulfan-based ( n  = 75) MAC regimens at our institute. After adjusting for significant variables in the univariate analysis, there were no significant differences in neutrophil recovery (hazard ratio (HR), 0.88; p  = .460), grade III–IV acute graft-versus-host disease (GVHD) (HR: 1.40, p  = .410), extensive chronic GVHD (HR: 0.73, p  = .380), relapse (HR: 0.61, p  = .270), non-relapse mortality (HR: 1.38, p  = .420), overall survival (HR: 1.18, p  = .637), or event-free survival (HR: 1.08, p  = .773), although platelet recovery was lower with marginal significance for the busulfan-based regimen (HR: 0.67, p  = .068). In subgroup analysis, TBI-based regimens were superior to busulfan-based regimens in terms of survival for acute lymphoblastic leukemia, but not for myeloid malignancies. Further investigation is warranted even for CBT.